Erect culm internodal anatomy and properties of sun ecotype of Imperata cylindrica (L.) P. Beauv - Sima, SN; Roy, AK; Joarder, N (Bangladesh Journal of Botany, 2015)
Internodal anatomy of Imperata cylindrica (L.) P. Beauv. was described in this paper. Culm internodes were completely encircled by leaf sheath. Peripheral vascular bundles were many in number and small in size. Central bundles were large in size and a few in number. Large bundles were of various sizes and vascular tissues well developed. Each vascular bundle had strong mass of sclerenchyma tissue arching over the phloem in the form of phloem hood. Small bundles were poorly developed in respect of vascular tissue. A small percentage of vascular bundle consisted of phloem tissue only fundamental ground tissues were parenchyma in nature. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22725 Bangladesh J. Bot. 44(1): 67-72, 2015 (March)